Use of SAPS 3, APACHE IV, and GRACE as prognostic scores for acute coronary syndrome patients in the cardiovascular care unit - Yudha, Tria; Prasetya, Indra (Universitas Brawijaya, 2025)
A grading system based on disease severity has been widely used in intensive care units (ICUs) since around 1980. These systems are used to predict mortality and assess severity in clinical trials. Simplified Acute Physiology Score 3 (SAPS3) and Acute Physiology and Chronic Health Evaluation Score (APACHE IV) are prognosis ratings that can predict in-hospital mortality within the first hour of ICU care. Although these technologies have been widely employed in the ICU, they have yet to be commonly deployed in the cardiovascular care unit (CVCU) due to different patient populations. Intensive care doctors typically employ the standard prognostic scores, SAPS3 and APACHE IV, which were generated from diverse populations of critically ill patients. Although these scores are the most widely used early versions, APACHE IV and SAPS 3 do not include acute coronary syndrome patients. The Global Registry of Acute Coronary Events (GRACE) score has performed the best; this may be because of its straightforward design, which does not distinguish between individuals with SCA and those without ST-segment elevation. Our review article attempts to evaluate the performance of standard predictor scores, namely SAPS 3, APACHE IV, and GRACE, on patients with cardiovascular emergencies. Thus, these score systems can precisely assess the relationship between mortality prediction scores and outcomes of patients admitted to the CVCU rapidly and comprehensively.